2021
DOI: 10.3390/ijerph18073504
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Family Functioning in Chinese Families of Children with Autism Spectrum Disorder

Abstract: Families caring for children with autism spectrum disorder (ASD) have reported poorer family functioning. Social support might strengthen family functioning, but limited research to date has focused on this association in China. This study conducted a cross-sectional survey of Chinese families that have children with ASD to examine the relationship between social support and family functioning. Caregivers of children with ASD from Sichuan province in China (N = 167) were surveyed concerning their perceived soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 45 publications
4
32
1
Order By: Relevance
“…These resources and supports may help individuals and their families to cope with the traumatic environment, and further contribute to the family adaption. A previous study found the effect of social support on family functioning in Chinese families of children with Autism Spectrum Disorder, which may provide support for our results [33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These resources and supports may help individuals and their families to cope with the traumatic environment, and further contribute to the family adaption. A previous study found the effect of social support on family functioning in Chinese families of children with Autism Spectrum Disorder, which may provide support for our results [33].…”
Section: Discussionsupporting
confidence: 89%
“…However, if an individual is exposed to a traumatic environment (often in the family) in childhood, this individual may be capable of changing or disengaging from the traumatic environment during adolescence through other supports and resources (e.g., communities, teachers, psychological counselors, and peers) because the person has a wider social circle during adolescence. A previous study also found that the social support of family members could affect family functioning [ 33 ]. Therefore, we hypothesized that social support may be an antecedent of family functioning in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with BD reported less social support than the general population, especially subjective support, which is consistent with the article by Lei and Kantor (2021). A previous study illustrated that subjective support was correlated with the behavior and development of patients as a psychological perception of reality (Lu et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…A previous study illustrated that subjective support was correlated with the behavior and development of patients as a psychological perception of reality (Lu et al, 2021). The assessment of the patient's satisfaction with being respected, understood, and supported in society is necessary when intervening in the social support of patients with bipolar disorder (Lei and Kantor, 2021). Although the measurements are inconsistent, the findings are consistent previous studies (Guerrero-Jimenez et al, 2021;Lei and Kantor, 2021) suggesting that social support is related to family functioning and psychosocial functioning.…”
Section: Discussionsupporting
confidence: 76%
“…Firstly, the better family relationships play as a foundation of BCE ( 44 ), which can promote the development of family-related BCE, increasing the protective effect of BCE on the US ( 55 ). Secondly, family is one of the most important resources of social support ( 68 ) and family resilience ( 60 ), the better relationship in the family often represents the higher family social support and family resilience, which can both enhance their BCE and enable them to flourish with warmth, support, and cohesion by successfully coping with the US ( 60 ). The attachment theory indicated that one's emotional needs can be satisfied by warm and supportive parenting and a positive family atmosphere, leading to less preoccupation with one's negative mild mental problems ( 69 ).…”
Section: Discussionmentioning
confidence: 99%